SELEKSI KETAHANAN BEBERAPA KULTIVAR PADI (Oryza sativa L.) LOKAL ASAL KALIMANTAN TIMUR TERHADAP CEKAMAN ALUMINIUM PADA FASE PERKECAMBAHAN - Nurul Aini; Susylowati Susylowati; Nurhasanah Nurhasanah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
Food security and sovereignty can be realized through the expansion of agricultural land to the marginal lands. One type of marginal land is acidie soils with high levels of aluminum (Al) toxicity. An efficient and environmentally friendly approach to utilizeng acidie soils as agricultural land is by using rice varieties which have a high tolerance to aluminum stress on acidie soils. The purpose of this study was to determine the effect of aluminum stress on the growth of the local rice from East Kalimantan and to select the tolerant cultivars against aluminum stress at the germination stage. The study was conducted for three months (May-July 2018), at Laboratory of Biotechnology, Faculty of Agriculture, University of Mulawarman, Samarinda. This study used a Split Plot Design with three replications. As the main plot was Aluminum stress concentration (A) consisting of 3 levels, namely 0, 250 and 500 ppm of AlCl3 and as subplots were 25 rice genotypes, consisting of 23 local rice cultivars from East Kalimantan (V) and two genotypes as tolerant (Mekongga) and sensitive (IR64) controls. Assessment of aluminum tolerance level was carried out by calculating plant sensitivity index values against aluminum stress based on the Relative Root Growth (RRG) and Relative Shoot Growth (SRG) parameters. Other plant growth parameter data, root and shoot fresh and dry weight, were analyzed using analysis of variance at the test level α = 0.05, and the post-hoch test using Honestly Significant Difference test (HSD). Aluminum stress caused disruption of the East Kalimantan local rice cultivars growth, especially root growth. Aluminum concentration at either 250 ppm or 500 ppm reduced relative root growth and further damage the root system of the rice plants causing roots stunted and thickened. Likewise with shoot growth parameter, there was a relative shoot growth decline due to the aluminum stress on the plants. Two local rice cultivars of East Kalimantan, Pulut Mayang and Pulut Linjuang, were consistently tolerant to aluminum stress either in 250 ppm or 500 ppm of AlCl3; while Kawit, Bentian, Mayas Putih and Ketan putih cultivars were only classified as tolerant at a concentration of 250 ppm aluminum. On the other hand, a control sensitive variety IR64 showed the susceptibility to 250 and 500 ppm aluminum stress.